POTENSI ALELOPATI EKSTRAK DAUN Gleichenia linearis (Burm.) Underw. TERHADAP PERKECAMBAHAN DAN PERTUMBUHAN ANAKAN GULMA Mikania micrantha (L.) Kunth - Awit Tatas Asih Susanti; Mayta Novaliza Isda; Siti Fatonah (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Gleichenia linearis is a wide-leaf weed that contains chemical compounds such as flavonoid, allelochemical, triterpenoid, saponin, tannin, alkaloid and steroid that can inhibit the growth of other plants so it can be used as bioherbicide. The aims of this study were to determine the potential of residues and the concentration of G. linearis leaf extract on germination and growth of seedling weed Mikania micrantha. This studywas conducted using completely randomized design with 5 replicates with three concentrations i.e. 10%, 20% and 30%. Data was observed and analyzed using Analysis of Variance (ANOVA) and tested using Duncan's Multiple Range Test (DMRT) if it showed significant effect. This study showed the decrease of growth and germination and the increase of the percentage of the death of M. micrantha weed after treatment of G. linearis leaf extract. The highest decrease was found in 30% extract concentration with the percentage of germination, fresh weight, the percentage of mortality were 19%, 0.436 g and 10%, respectively.